Recent advances in oncolytic virus combined immunotherapy in tumor treatment - Xiaoli Zhou; Shunfeng Hu; Xin Wang (Genes and Diseases)
Oncolytic viruses (OVs), a kind of emerging therapeutics for treating tumors, are characterized by high replication efficiency, superior killing effects, and few adverse reactions, which have shown great application prospects in preclinical tumor treatment trials. To overcome the limitations of OV monotherapy, recent studies have found that combination therapy with other anti-tumor therapeutics, especially with immunotherapy, yields promising outcomes in tumor eradication. Due to the advancements in genetic engineering, the combination of OVs with novel immunotherapy, including cellular immunotherapy, adoptive cellular immunotherapy, immune checkpoint inhibitors, cancer vaccines, cytokines, and bi- or tri-specific T cell engagers, has greatly improved clinical outcomes and quality of life of tumor patients. In this review, we systematically summarize the latest progress of OVs combined with immunotherapy in tumor treatment and highlight the future directions of the combination strategies, which will promote the clinical application of OVs in tumor therapy.